Study of the dairy characters of lactating Murrah buffaloes on the basis of body parts measurements - Sandeep Dhillod; Dipankar Kar; C. S. Patil; Subhasish Sahu; Narender Singh (Veterinary World, 2017)
Aim: The aim of the study was to correlate the milk yield of Murrah buffaloes with certain body parts measurements. Materials and Methods: A total of 70 lactating Murrah buffaloes were selected from Buffalo Farm, Lala Lajpat Rai University of Veterinary and Animal Science, Hisar and were randomly selected in a range from first to fifth parity. Traits studied were 305 days milk yield (MY), body weight (BW), body length (BL), muzzle width (MW), height at wither (HW), abdominal girth (AG), chest girth (CG), body depth fore, body depth rear, hip bone distance (HBD), pin bone distance (PBD), skin thickness (STK), and tail length (TL). Data were collected and statically analyzed by Pearson’s correlation method. Result: The result of this study showed that Murrah buffaloes had the average 2604.8±39.5 kg for MY, 556.1±4.9 kg for BW, and 152.2±0.8 cm for BL. This study showed that buffaloes had positive significant (p<0.05) correlation between MY and BW (0.26). Highly significant (p<0.01) correlation was observed between MY and AG (0.64), MW (0.42). Significant (p<0.01) negative correlation was observed between MY and STK (−0.79). Different body part measurements (BW, BL, HW, AG, CG, MW, TL, BD, PBD, HBD, STK) were significantly correlated with each other. Conclusion: This study can be helpful as a selection tool to enhance and evaluate the production potential by setting standards of Murrah buffalo breed. BW, abdominal growth, muzzle thickness, and STK were found key factors while selecting a dairy Murrah buffalo.